Towards actualizing the power of knowledge in religions / Siti Fatahiyah Mahamood - Mahamood, Siti Fatahiyah (UPENA, 2006)
Religion is an important element which has all the hallmarks of full respective cultural system. Religion is also defined as a belief in the ultimate reality that helps to uncover the meaningfulness in the midst of the mundane by exploring the transpersonal dimension of the internal and infinite life. Hence, all religions in this universe always encourage the people to seek and acquire knowledge as it plays a vital role in the entire aspect of human lives. According to Locke, all of men that we met; nine parts of them are what they are good or evil, useful or not, is being judged by their education. Alvin Toffler says in his book of Powershift that the new accelerated system for wealth creation is increasingly dependent on the exchange data, information and knowledge. It is 'super-symbolic' that wherever no knowledge is exchanged, no new wealth is created. Thus, this paper is concisely prepared in order to explore the power of knowledge in the respective religions. This article concludes that a person who has knowledge is definitely not equal to a person who does not. Those who have knowledge are aware of the truth and act accordingly, thereby having a beneficial impact on those around them whereas those who are ignorant fumble through the world, vainly attempting to satisfy their desires and ultimately failing to gain consciousness of their purpose and duty in this life. It should be clear that knowledge is a means to an end. This is because knowledge revives the dead hearts and drives them out of darkness into light, and because knowledge is the light of the inner eyes that cures one's blindness and restores his inner sight.